2009
DOI: 10.1128/aem.00972-09
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 Strains That Persist in Feedlot Cattle Are Genetically Related and Demonstrate an Enhanced Ability To Adhere to Intestinal Epithelial Cells

Abstract: A longitudinal study was conducted to investigate the nature of Escherichia coli O157:H7 colonization of feedlot cattle over the final 100 to 110 days of finishing. Rectal fecal grab samples were collected from an initial sample population of 788 steers every 20 to 22 days and microbiologically analyzed to detect E. coli O157:H7. The identities of presumptive colonies were confirmed using a multiplex PCR assay that screened for gene fragments unique to E. coli O157:H7 (rfbE and fliC h7 ) and other key virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 54 publications
1
49
1
Order By: Relevance
“…Other studies observed intermittent shedding of STEC by adult dairy cows, each animal potentially shedding for several months (63,(99)(100)(101). Similar intermittent shedding patterns have been observed in feedlot cattle (58,102). Individual and herd shedding patterns have been associated with several factors, including diet, herd size, housing type, and age of the animal (3).…”
Section: Discussionmentioning
confidence: 70%
“…Other studies observed intermittent shedding of STEC by adult dairy cows, each animal potentially shedding for several months (63,(99)(100)(101). Similar intermittent shedding patterns have been observed in feedlot cattle (58,102). Individual and herd shedding patterns have been associated with several factors, including diet, herd size, housing type, and age of the animal (3).…”
Section: Discussionmentioning
confidence: 70%
“…This characterization was aimed at identifying strain-specific traits that would be necessary for attaining supershedder levels in the lower GI tract of cattle. To address this issue, it was deemed a high priority to collect samples from a diverse group of cattle, as previous studies have reported dominant E. coli O157:H7 genotypes within individual feedlots (29,30). This priority led to the collection of a majority of the samples from cattle at harvest.…”
Section: Resultsmentioning
confidence: 99%
“…A 1-year survey of Alberta dairies yielded 65 isolates of EC H7 grouped into 23 PFGE 2-enzyme profiles; 60=65 belonged to three patterns with >90% homology . In a long-term study of EC O157:H7 carriage by feedlot cattle, 132 isolates were divided into 32 PFGE types; one type accounted for 53% of all isolates, and showed high adherence to Caco-2 cells (Carlson et al, 2009). Persistent and dominant strains may be those that can easily colonize cattle and survive in the farm environment; the pen prevalence may be continuous for 5 months, and a given strain may persist on a farm for >2 years (Shere et al, 1998).…”
Section: Ehec In the Farm Environmentmentioning
confidence: 99%